Discussions on education in Serbia during the COVID-19 lockdown: A twitter-based analysis - Jovanović Olja; Gagić Dragana; Radaković Tatjana; Barišić Milica; Vulić Šimšić Ivana (Psihološka Istraživanja, 2025)
The COVID-19 pandemic led to unprecedented changes in different aspects of human life, including a significant impact on education systems. This study aimed to explore the public perception of education during the initial five weeks of emergency remote education (ERE) in Serbia in response to the COVID-19 outbreak. In a fiveweek timeframe starting from March 17, 2020, we collected tweets on the topic of education using MAXQDA software, resulting in a final dataset of 1,777 tweets. The tweets were analyzed using qualitative content analysis and interpreted through the lens of Cultural-Historical Activity Theory. The results of the research show a decreasing trend in the frequency of posts related to education, starting from 1,402 in the first week to 92 tweets in the fifth week. The emotional tone of the tweets was predominantly negative in the first five weeks of the pandemic, with the percentage of tweets with a negative connotation increasing over time. The analysis of the content of the tweets highlights key themes of public discussion and reveals contradictions between ERE and pre-pandemic schooling. The Twitter community praised the use of new tools and teachers' efforts but criticized adherence to rules of conventional schooling, as well as the learning content for being overly demanding and irrelevant. The study results suggest that ERE during the lockdown increased the visibility of teaching, offering potential for democratization of education, while the invisibility of learning created risks to educational equity by obscuring the struggles of learners.